2012
DOI: 10.1002/cbic.201100808
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Heme b into the Structure of the Cys34‐Carbamidomethylated Human Lipocalin α1‐Microglobulin: Formation of a [(Heme)21‐Microglobulin)]3 Complex

Abstract: α(1)-Microglobulin (α(1)m) is a 26 kDa plasma and tissue protein belonging to the lipocalin protein family. Previous investigations indicate that the protein interacts with heme and suggest that it has a function in heme metabolism. However, detailed characterizations of the α(1)m-heme interactions are lacking. Here, we report for the first time the preparation and analysis of a stable α(1)m-heme complex upon carbamidomethylation of the reactive Cys34 by using recombinantly expressed human α(1)m. Analytical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…A1M is a 26 kDA glycoprotein belonging to the Lipocalin family with immunoregulatory characteristics and is involved in heme catabolism [41]. Bikunin is a Kunitz-type serine protease inhibitor of the inter- α -inhibitor family and a structural component of the extracellular matrix [23, 42].…”
Section: Resultsmentioning
confidence: 99%
“…A1M is a 26 kDA glycoprotein belonging to the Lipocalin family with immunoregulatory characteristics and is involved in heme catabolism [41]. Bikunin is a Kunitz-type serine protease inhibitor of the inter- α -inhibitor family and a structural component of the extracellular matrix [23, 42].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the cell cytosol and thiol groups of cytosolic proteins of the erythroid cell line K562 were reduced by A1M [39]. Furthermore, A1M reduced the number of carbonyl groups on oxidized collagen in a reaction which was entirely dependent on the presence of Cys34, [43]. A possible heme-binding site consisting of a Cys-Pro-dipeptide motif similar to those seen in the cytochrome P450 family is located at loop 1 (Cys34-Pro35) [8] (Figure 2).…”
Section: Reductionmentioning
confidence: 99%
“…The g Ќ value of 5.75 was too low for a pure high spin state. Based on the pH-independent g Ќ value of 5.75, the spin state is best described as a quantum spin admixture having 12% of an S ϭ 3/2 iron spin state with unresolved g 1 and g 2 (37,38).…”
Section: Heme Iron Spin State and Coordinationmentioning
confidence: 99%